Beyond Europe: Integrated Markets in Other Parts of the World - Küpper, Herbert (Maastricht 30: A Central European Perspective, 2025)
The internal market of the European Union is the highest level of economic integration in the world. However, it is not the only international instrument for market integration. Both in Europe and beyond, we find many international organisations that aim at, and sometimes achieve, some degree of economic cooperation and integration. These may be classified as free trade zones, customs unions, common markets, economic unions, and currency unions. The EU is partly an economic union and partly, forthe states of the Eurozone, a currency union. A comparative analysis of other international organisations reveals that the special feature of the EU is its supranationality, a feature that even the currency unions in the Caribbean and Africa lack.Keywords: European Union, internal market, supranationality, international economic organisations